Before Victoria : extraordinary women of the British Romantic era - Denlinger, Elizabeth Campbell (New York Public Library : Columbia University Press, 2005)
Combining literary and cultural history, this richly illustrated volume brings back to life a remarkable, though frequently overlooked, group of women who transformed British culture during the Romantic era and inspired new ways of understanding feminine roles and female sexuality. Often working from home, women wrote novels and poetry, sculpted busts, painted portraits, and conducted scientific research. This book makes full use of The New York Public Library's extensive collections to depict these women, their works, and their social and domestic worlds.